Synthesis of graphene and carbon nanotube composite by chemical vapor deposition - Yu, Hong. (2011)
Two-dimensional (2D) material Graphene and 1D carbon nanotubes (CNTs) are attractive materials with a series of potential applications due to their outstanding and unprecedented electronic, thermal and mechanical properties. The combination of graphene and CNTs may create a new 3D composite material (graphene/CNT), which would have interesting properties and also serve as a new building block in nanotechnology.